Are female drum players a taboo in Candomble? Problems of gender and power in the symbolic territory of the Candomblé sacred drums (Ágora Journal, 2025)
The Candomblé religion is known in Brazil for its established hierarchy of power based on seniority and the distribution of roles and tasks according to gender. In all the available literature considered classic on Candomblé rituals, we find, for example, mention of the positions of alabês and ogans de toque, as honorary positions exclusively for men, intended for the technical care, learning, and transmission of the sound liturgy involving the consecrated drums, on the one hand, and on the other, the reinforcement of a belief that the presence of women in this symbolic territory is not permitted. Despite this supposed taboo, we have found female sacred drummers who subvert a supposed “secular prohibition” today in the Candomblé terreiros of Bahia and, based on their biographical accounts, an in-depth bibliographic review on the subject, an analysis of some mythopoetic texts, and an iconographic selection, we aim to understand whether these female presences in the sacred drums of some candomblés are a new and growing phenomenon or vestiges of a dimension of the cult that was erased by the impact of patriarchal cultures.
Keywords: genders problems; candomble; cultural taboo; afroreligiosity.